Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Quality-oriented radio-frequency heating of leguminous vegetables: Multi-criteria optimisation and predictive modelling for process-quality control - Yandi Zeng; Da Tang; Youshan Zhang; Lisha Yang; Shaojin Wang; Zhi Huang (Food Control, 2026)

Temperature-regulated surfactant interfacial behavior influences shell formation and mechanical susceptibility of pesticide microcapsules - Xuewen Jian; Xin Liu; Quanbin Liu; Haixiu Bai; Xiangyang Li; Yunyu Tang; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

Productive, physiological, and biochemical responses of elephant grass ‘BRS Capiaçu’ (Pennisetum purpureum Schumach.) under different water regimes with brackish water in a semi-arid environment - Lara Rosa de Lima-Silva; Lady Daiane Costa de Sousa Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Wagner Martins dos Santos; Pedro Paulo Santos de Souza; Luciana Sandra Bastos de Souza; Cleber Pereira Alves; Agda Raiany Mota dos Santos; Ênio Farias de França e Silva; Hugo Rafael Bentzen Santos; Wilma Roberta dos Santos; Carlos André Alves de Souza; et al. (Physiology and Molecular Biology of Plants, 2026)
The seasonality of forage production is one of the main challenges in semi-arid regions, where environmental conditions limit agricultural productivity. One promising option is the use of elephant grass ‘BRS Capiaçu’, together with deficit irrigation. This study evaluated the impact of different irrigation depths with brackish water (50%, 75%, 100% and 125% of the reference evapotranspiration – ET 0 ) on the productive, physiological, photochemical and biochemical aspects of ‘BRS Capiaçu’ over two cycles. Irrigation with 50% of the ET 0 resulted in lower rates of net photosynthesis (P n ), with a reduction in photosystem II quantum yield (ΔF/Fm’), qP, NPQ and the electron transport rate (ETR), in addition to greater activity of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX), indicating oxidative stress. The depths of 50% and 100% of the ET 0 resulted in greater dry matter production, for Cycles 1 and 2, respectively, demonstrating the resilience of the crop to water stress, attributed to such mechanisms of acclimatisation as a reduction in transpiration (T r ) and an increase in water use efficiency. These physiological changes were more obvious during Cycle 2, in which the crop was subjected to lower rainfall (47.8 mm), while salt stress was also more pronounced during this period, in response, the plants showed less water loss through transpiration and larger WUE inst . It was concluded that ‘BRS Capiaçu’ has a high capacity for acclimatisation to semi-arid conditions, and stands out as a viable alternative for mitigating the seasonality of forage production and promoting sustainable livestock farming in the region.

A scalable framework for synthesizing conditional porous media images using diffusion and GAN models - Atheer Dheyauldeen; Ying Da Wang; Kunning Tang; Ryan T. Armstrong; Peyman Mostaghimi (Advances in Water Resources, 2026)

Proximal-distal coordination engineering of iron single-atom nanozyme for synergistic multi-enzymatic-photothermal control of antibiotic-resistant bacteria - Yunsen Wang; Zhichao Yu; Xiuhui Liang; Zhilan Bi; Minglang Zou; Shuo Tian; Da Huang; Zuquan Weng; Dianping Tang; Jinfeng Kong (Journal of Hazardous Materials, 2026)

Ultrasound-pretreated radio frequency heating for efficient walnut kernel peeling: Process optimisation and quality preservation - Jiaqi Ma; Da Tang; Le Liu; Yandi Zeng; Pengyu Qin; Shaojin Wang; Zhi Huang (Innovative Food Science & Emerging Technologies, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Molecular epidemiology and genetic diversity of carp edema virus (CEV) in China (2013–2019): New insights into transmission and diagnosis - Tinhan Chien; Chuwei Ma; Junqi Wang; Weizhong Tian; Shifu Kan; Xuebing Yang; Shaolin Tang; Meiting Lee; David Stone; Sophie St-Hilaire; Hsien-Da Huang; Hong Liu; et al. (Aquaculture, 2026)

Aged nanoplastics exacerbate CPPD-induced ocular toxicity via the thyroxine pathway in zebrafish - Jin Li; Yi Zheng; Yuying Yin; Wenda Gao; Fan Tang; Xinlin Zhao; Qi Xin; Suiyi Liu; Jiaqi Xiong; Jian Lin; Da Sun; Jiangfei Chen (Aquatic Toxicology, 2026)

Effects of radio frequency heating on fruit and vegetable quality: mechanisms, physicochemical changes, and processing applications - Yandi Zeng; Pengyu Qin; Da Tang; Le Liu; Yinuo Jiang; Shaojin Wang; Zhi Huang (Critical Reviews in Food Science and Nutrition, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Machine learning-enhanced UAV multispectral remote sensing for monitoring rice leaf area index across critical growth stages - Chao Su; Zaiying Ling; Liwang Han; Yanmin Shuai; Jianguang Wen; Xingwen Lin; Haifeng Tang; Alexandre Maniçoba da Rosa Ferraz Jardim; Hoi Leong Lee; Xuguang Tang (Precision Agriculture, 2026)

Biogeochemical evolution and iron speciation in the abandoned Yellow River Delta: deciphering the impact of anthropogenic engineering and introduced Spartina alterniflora - Zisheng Zhang; Hepin Wu; Qiao Li; Xiao Tang; Hongwu Zhou; Da Li (Frontiers in Marine Science, 2026)
Understanding sediment dynamics and anthropogenic impacts in the land-sea interaction zone of the Abandoned Yellow River Delta is challenged by complex material sources. This study aims to reconstruct sedimentary environment evolution and evaluate human influences on silty-mud tidal flats. Sediment cores were collected from a bare flat (GT) and a Spartina alterniflora marsh (HM) in the Yancheng coastal wetland, Jiangsu, China. A multi-proxy approach was applied, including grain size, organic carbon and nitrogen content, 210 Pb - 137 Cs dating, analysis of major elements and iron speciation analysis. Results indicate: (1) The GT core exhibits sandy silt characteristics, indicative of an intertidal environment. The HM core is dominated by clayey silt and silt, displaying a silt-sand binary structure, reflecting a typical silty tidal flat. Grain size characteristics suggest tidal flat accretion is collectively driven by reclamation, storm surges, tidal action, and sediment trapping by S. alterniflora . (2) Organic matter provenance analysis reveals marine sources dominate the GT core, while terrigenous sources dominate the HM core. Increasing trends of TOC, TN, and C/N with depth suggest S. alterniflora introduction likely promoted organic matter accumulation. (3) 210 Pb - 137 Cs dating yields deposition rates of 1.25 cm/a (GT) and 1.39 cm/a (HM). Combined with previous studies, regional average deposition rates show a declining trend with enhanced accretion, potentially linked to increased hydrodynamics from reclamation and the Jiangsu Coastal Current. (4) Major elements follow the Na > Al > K > Fe > Ca > Ti > Mg > Ba > Mn > Sr and the distribution of major elements is synergistically controlled by provenance, grain size effects, and biological processes; the variations in element-grain size correlations reveal the modulating effect of sedimentary composition on geochemical behavior. (5) Iron speciation content follows the order Fe ox > Fe mag > Fe carb > Fe py and increases with depth, primarily sourced from terrigenous inputs influenced by chemical weathering and marine dynamics. The sedimentary environment is oxic/suboxic, promoting TOC mineralization and hindering preservation. The Fe HR /Fe T ratio characteristics resemble those of shelf-margin marine sediments and Yellow River particulates. However, influenced by weathering, runoff, and sea-level changes, this ratio is unreliable for accurately indicating redox conditions.

Multidimensional dissection of shared genetic susceptibility in ulcerative colitis and colorectal cancer: novel insights from integrative single-cell and multi-omics analysis - Fanfan Zhu; Xin Yao; Da Liu; Shanshan Wang; Xuyu Huang; Jing Zhou; Song Wang; Shanneng Tang; Dongping Lai; Shuang Yang; Xiaobing Meng; Xinyue Zhang; et al. (Inflammation Research, 2026)

A core-shell fiber membrane with synergistic radiative cooling and thermal buffering for all-weather personal comfort - Xiaohong Wu; Akbar Bashir; Chak-Yin Tang; Gary Chi-Pong Tsui; Ziqi Li; Nanhao Chen; Yichi Zhang; Yan Chen; Jie Cui; Juncheng Zhuang; Chen Liu; Yuanyuan Li; et al. (Chemical Engineering Journal, 2026)

Integrative analysis of transcriptome dynamics and Notch signaling pathways reveals molecular basis of egg quality in Plectropomus leopardus - Mingjian Liu; Mengya Wang; Chaofan Jin; Jiahang Li; Da Zheng; Haizhan Tang; Zhongyi Zhai; Zhenmin Bao; Bo Wang; Jingjie Hu (Aquaculture, 2026)

Energy-efficiency optimization of tunnel lighting systems: an adaptive penalty function model considering combined parameters of inner wall reflectivity and luminaire layout - Hao Liu; Shiyong He; Weidong Tang; Da Xu; Jia’an Niu; Xin Tang; Zhonglang Yang; Bo Liang (Tunnelling and Underground Space Technology, 2026)

Effects of hot air pretreatment on digestibility and quality of steamed bread - Yuze Jia; Jun-Hu Cheng; Xiangwei Tang; Xucong Yu; Da-Wen Sun (Food Chemistry, 2026)

Cold plasma-assisted enzymatic hydrolysis of shrimp protein for bioactive peptide production: Structural, antioxidant, and molecular docking characterization - Caidie Tang; Jun-Hu Cheng; Jilin Li; Da-Wen Sun (Food Chemistry, 2026)

Stress-induced orbital splitting and lone-pair modulation in anharmonic phonon transport of BiAgSeO superlattice - Shuwei Tang; Yufei Meng; Pengfei Zhang; Da Wan; Peng Ai; Zhiwei Zhang; Ying Liu; Zhanpeng Xu; Hao Sun; Shulin Bai (Chemical Engineering Journal, 2026)

Tuning d-f hybridization to mimic haloperoxidase for microneedle-assisted targeted therapy of drug-resistant infections - Zhichao Yu; Fengrui Gao; Minglang Zou; Man Xu; Sufang Liu; Da Huang; Zuquan Weng; Yongyi Zeng; Dianping Tang; Xiaolong Liu (Chemical Engineering Journal, 2026)

A General Kinematic Brain Injury Criterion Combining Translational and Rotational Effects - Yuting Zhang; Da Teng; Zexuan Chen; Bao Yang; Zhenyu Jiang; Yiping Liu; Zejia Liu; Licheng Zhou; Liqun Tang (Annals of Biomedical Engineering, 2026)

In situ amidation of NH3 in biogas on sludge-derived carbon to promote coexisting CO2 adsorption - Zhangliang Han; Aoran Zhang; Shuofei Yuan; Xinyue Lu; Shuangxi Fang; Juntao Tang; Da Wang; Zhiqiao He; Feilong Dong; Shuang Song (Water Research, 2026)

Isolation, purification, and functional characterization of porcine fibroblasts across different ages and anatomical sites for cultured meat - Wei Li; Chunyan Da; Moru Deng; Shijie Ding; Shuyu Pan; Xinyue Liang; Chunbao Li; Guanghong Zhou; Changbo Tang (Food Research International, 2026)

Polycrystalline ferroelectricity in a molecular crystal for piezoelectric sensing - Gele Teri; Jing-Song Tang; Peng-Cheng Zhuge; Jia-Qi Luo; Hao-Fei Ni; Lei Pan; Qiang-Qiang Jia; Yi Zhang; Da-Wei Fu; Zhi-Xu Zhang (Chemical Engineering Journal, 2026)

Precooling effectiveness in residential buildings during heatwaves with power outages: A sensitivity and parametric analysis - Xue Liu; Hao Tang; Xuyuan Kang; Pengyuan Shen; Xin Zhou; Da Yan (Building and Environment, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Utilising micro-CT to analyse fluid dynamics in dual-porosity packing systems - Quan Zheng; Kunning Tang; Ying Da Wang; Samuel J. Jackson; Thomas Poulet; Ryan Armstrong; Peyman Mostaghimi (Hydrometallurgy, 2026)

Satellite evidence for persistent degradation in Brazil's desertification nuclei - Alanderson Firmino de Lucas; Marcos Vinícius da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; Gabriel Thales Barboza Marinho; Lady Daiane Costa de Sousa Martins; João Emanoel Ambrósio Gomes; Gledson Luiz Pontes de Almeida; Jhon Lennon Bezerra da Silva; Wilma Roberta dos Santos; Wagner Martins dos Santos; Elania Freire da Silva; et al. (Remote Sensing Applications: Society and Environment, 2026)

The soil plastisphere: A hotspot for arsenic methylation regulated by microplastic polymer types - Kaimei Zhang; Wei Feng; Qingnan Huang; Williamson Gustave; Yimin Cai; Da Ouyang; Mei Li; Xianjin Tang; Haibo Zhang; Ting Guo (Environmental Research, 2026)

3D porous media image synthesis using conditional GAN - Atheer Dheyauldeen; Ying Da Wang; Kunning Tang; Ryan T. Armstrong; Peyman Mostaghimi (Computers & Geosciences, 2026)

Key factors affecting atmospheric visibility during the 19th Asian Games in Hangzhou - Yang Wu; Jing Wei; Jiasi Shen; Xiaoyuan Wang; Zheng Xia; Wenlong Zhao; Da Xu; Qian Tang; Jinmei Ding; Xudong Tian; Yuwen Niu; Zhibin Wang; et al. (Atmospheric Research, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

The Effect of Density Difference on the Sedimentation Dynamics of Two Spherical Particles in Side-by-Side and Tandem Configurations - Da Hui; Xiang Ji; Baizhuang Chen; Mingfu Tang; Lixin Xu (Journal of Marine Science and Engineering, 2025)
Complex fluid–particle interactions are ubiquitous in natural environments and engineering applications, with their underlying mechanisms often attributed to interparticle attraction and repulsion. To understand the interaction mechanism between the dual particles, this study examines the setting process of dual particles using the Immersed Boundary-Lattice Boltzmann Method (IB-LBM), with a focus on the effect of the density difference between particles. Two typical configurations—tandem and side-by-side—are considered in the analysis. In the tandem configuration, when ρLP/ρTP 1, kissing between two particles is mainly determined by the density of LP. Whether kissing occurs between the two particles depends on a critical value ρLP/ρTP=1.2:1.14. Although the LP’s attraction to the TP strengthens with increasing LP density, beyond this certain threshold, this attraction becomes insufficient for the TP to catch up with the LP. In a side-by-side configuration with two particles of different densities, their interaction evolves from initial attraction to subsequent repulsion. This phenomenon is not observed in pairs of particles with identical density. Moreover, with increasing density difference between the particles, the attractive effect from the higher-density particle on the lower-density one strengthens, whereas the repulsive interaction between them gradually weakens. When the particle density ratio reaches 1.4:1.14, the lateral migration of the particles becomes very small; although they still interact with each other, the effect becomes extremely weak. This work systematically elucidates the influence of density disparity on particle interaction, providing insights into understanding more complex multiparticle system dynamics.

Additive effects of Lp(a) and inflammation on cardiovascular risk beyond LDL-C lowering: circulating and genetic evidence from 401,548 adults - Rui Li; Wenyue Dong; Wenxiu Wang; Youling Duan; Miao Zhang; Tao Huang; Xinwei Hua; Yi-Da Tang (Science Bulletin, 2025)

Boosting the electro-Fenton process with a functionalized ACF cathode: Simultaneous H2O2 production and Fe2 + regeneration for rapid bisphenol A degradation - Juntao Tang; Yuhao Wu; Guanlong Wang; Mengyi Cao; Junxi Song; Da Wang; Weiting Yu; Yan Yu; Zhiqiao He; Shuang Song (Journal of Environmental Chemical Engineering, 2025)

Chemo-biostratigraphy of the Dzabkhan Craton: Refining the Ediacaran-Cambrian Transition in Southwestern Mongolia - Xiao Tang; Da Li; Simon V. Hohl; Michael Steiner; Ben Yang; Yi-Sheng Yin; Zhong-Lai Zhou; Qiao Li; Min Wu (Global and Planetary Change, 2025)

A Bayesian–physics integrated optimization framework for flexible building cooling under heatwave conditions - Xinyi Liu; Xue Liu; Yang Geng; Da Yan; Shan Hu; Hao Tang (Energy and Buildings, 2025)

Stacking-driven Na-bilayer cross vibration and band convergence in Na2CuZnSeP superlattice thermoelectric material - Pengfei Zhang; Yufei Meng; Shulin Bai; Da Wan; Peng Ai; Zhiwei Zhang; Yunzhuo Zhang; Zhanpeng Xu; Yujie Bao; Shuwei Tang (Chemical Engineering Journal, 2025)

Enrichment and metabolic truncation of comammox Nitrospira for driving partial nitritation in the mainstream anammox process - Da Jin; Xiaonong Zhang; Xingxing Zhang; Naif Abdullah Al-Dhabi; Wangwang Tang; Peng Wu; Aijie Wang (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

Divergent drought-induced suppression on vegetation and associated feedbacks: Satellite-based observations in 2022 across the Yangtze River basin, China - Lei Han; Yanan Chen; Chaoyang Wu; Li Yao; Ying Wang; Chao Su; Xuan Li; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; Xuguang Tang (Journal of Hydrology, 2025)

Enhancing coal seam gas recovery through greenzyme-induced relative permeability optimisation: Helium-driven core flooding experiments and field-scale production simulations - Wen Xi; Kunning Tang; Ying Da Wang; Yu Jing; Joan Esterle; Klaus Regenauer-Lieb; Lucas Evangelista; Ryan T. Armstrong; Peyman Mostaghimi (International Journal of Coal Geology, 2025)

Effects of cold plasma-assisted alcalase on the structure, allergenicity and epitopes of shrimp tropomyosin - Caidie Tang; Jun-Hu Cheng; Hangyu Zhong; Jilin Li; Da-Wen Sun (Food Chemistry, 2025)

Multidimensional mechanisms of biochar in mitigating Fe(III) stress in anammox consortia - Luomiao Ji; Xiaonong Zhang; Xingxing Zhang; Naif Abdullah Al-Dhabi; Wangwang Tang; Da Jin; Peng Wu (Environmental Research, 2025)

Recent advances in non-precious metal electrocatalysts for anion exchange membrane water electrolysis: Mechanistic insights, catalyst design, and structural regulation strategies - Qing Wang; Yuan Wang; Hon Man Luk; Jihui Tang; Shuang Wu; Dongyang Wu; Zhongyuan Hu; Da Cui; Jinghui Zhang (Chemical Engineering Journal, 2025)

Siloxene coupled graphene anode membrane with Zn-ion intercalation for all-solid-state Zn-ion hybrid supercapacitors - Erhui Zhang; Da Xie; Yuchen Hong; Zhenzhen Hui; Yongsheng Zhou; Shengbiao Zheng; Jiahao Guo; Zirong Li; Jie Chen; Jing Tang (Chemical Engineering Journal, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Unveiling the key drivers and formation pathways for secondary organic aerosols in an eastern China megacity - Fei Zhang; Jiasi Shen; Da Xu; Jiandong Shen; Yiming Qin; Ruifang Shi; Jing Wei; Zhengning Xu; Xiangyu Pei; Qian Tang; Hui Chen; Bingye Xu; et al. (Journal of Hazardous Materials, 2025)

Non-targeted and suspect screening analysis of non-phthalate ester plasticizers in house and car dust - Ning Zhang; Fengli Zhou; Long Zhang; Bize Lai; Shuqin Tang; Xiaotu Liu; Da Chen (Journal of Hazardous Materials, 2025)

Complementary regulatory mechanisms of Fe(II) and Fe(III) on anammox bacteria under low ammonium stress - Bo Gao; Xiaonong Zhang; Xingxing Zhang; Naif Abdullah Al-Dhabi; Wangwang Tang; Da Jin; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Reducing anti-nutritional factors in pea protein using advanced hydrodynamic cavitation, ultrasonication, and high-pressure processing technologies - Gaoya Dong; Zhipeng Hu; Jiafei Tang; Rahel Suchintita Das; Da-Wen Sun; Brijesh K. Tiwari (Food Chemistry, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Intercalation-driven interlayer dual-mode vibration in Bi6Cu2Se2Te2O6 superlattice thermoelectric material - Pengfei Zhang; Shuwei Tang; Yufei Meng; Ying Liu; Da Wan; Peng Ai; Zhiwei Zhang; Yunzhuo Zhang; Shulin Bai (Chemical Engineering Journal, 2025)

Characterizing Gut Microbiota Composition and Its Correlation with Growth Variation in Sea Cucumber Apostichopus japonicus - Xinyue Tang; Ziming Li; Xinghai Liu; Yulong Wu; Kaiqi Gong; Ying Guo; Wenbing Zhang; Shuyan Chi; Shilin Liu; Da Huo; Yujia Yang (Marine Biotechnology, 2025)

Structure-activity relationships and activity enhancement techniques of marine bioactive peptides (MBPs) - Cai-die Tang; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Polymer semiconductor-coated 3D bilayer cellulose nanofiber/polydimethylsiloxane aerogel for enhanced solar-driven interfacial water evaporation - Keerthnasre Dhandapani; Gayoung Ham; Hossein Fattahimoghaddam; In Ho Kim; Hyojung Cha; Xiaowu Tang; Da Wan Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2025)

Pluripotent stem cell-derived cardiomyocyte transplantation: marching from bench to bedside - Yi Hong; Jiarui Liu; Weixuan Wang; Hao Li; Weijing Kong; Xiaoxia Li; Wei Zhang; Sara Pahlavan; Yi-da Tang; Xi Wang; Kai Wang (Science China Life Sciences, 2025)

Assessment of heavy metal contamination and health risks in urban road dust and green belt soil: a case study in Harbin City, China - Ye Zhang; Si-Da Meng; Jian-Xin Wang; Jie Hu; Han Wu; Vasiliy Egorovich Kolodeznikov; Evgeniy Sergeevich Zakharov; Sakhayana Nikolaevna Danilova; Zhong-Hua Tang; Zi-Feng Zhang (Environmental Geochemistry and Health, 2025)

Extracellular polymeric substance-intercalated MXene membrane for osmotic power generation - Da-Qi Cao; Kai Tang; Guri Yihuo; Yan Jin; Yi-Xuan Song; Yun-Feng Wu; Wen-Yu Zhang; Zhongguo Zhang; Ming-Guo Ma; Li Song; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Bridging micro-to-nano scales for metal ore characterization via one-shot super-resolution - Kunning Tang; Ying Da Wang; Peyman Mostaghimi; Yufu Niu; Ryan T. Armstrong; Yulai Zhang; Lachlan Deakin; Lydia Knuefing; Mark Knackstedt (Minerals Engineering, 2025)

Cobalt-rich porphyry deposits derived from multiple mafic magma injections - Peng-Fei Shan; Ming-Jian Cao; Dong-Mei Tang; Zheng-Jie Qiu; Noreen J. Evans; Marina Lazarov; Da-Chuan Wang; Wei Hu; Ke-Zhang Qin; Ingo Horn; Stefan Weyer (Geochimica et Cosmochimica Acta, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Large-scale protein extraction from oat hulls using two hydrodynamic cavitation techniques: A comparison of extraction efficiency and protein nutritional properties - Jiafei Tang; Gulden Goksen; Md Saiful Islam; Vivek Ranade; Shay Hannon; Da-Wen Sun; Brijesh K. Tiwari (Food Chemistry, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Hydrologically-induced crustal stress changes and their association with seismicity rates in Taiwan - Ya-Ju Hsu; Roland Bürgmann; Zhongshan Jiang; Chi-Hsien Tang; Christopher W. Johnson; Da-Yi Chen; Hsin-Hua Huang; Miao Tang; Xinghai Yang (Earth and Planetary Science Letters, 2025)

Dual role of multistage inoculation in manipulating bacterial community assembly patterns to improve degradation of lignocellulose during rice or corn straw composting - Da Liu; Ziwei Jiang; Wenxuan Feng; Yufeng Zhao; Pengfei Tang; Jizhe Cui; Zhan Zhao; Qian Lu (Chemical Engineering Journal, 2025)

Declining trends and regional variations of organophosphate ester contamination in indoor dust from mainland China: Insights from a filed study and meta-analysis - Jing Li; Liu Yang; Yuying Ding; Fei Yang; Hongli Tan; Shuqin Tang; Da Chen (Science of The Total Environment, 2025)

Enhanced degradation of ofloxacin by novel zero-valent iron particles@V2C MXene composites with efficient activation of peroxomonosulfate: Mechanistic insights and DFT calculations - Yalei Zhou; Zhi Tang; Xiaoli Zhao; Fengchang Wu; Fazhi Xie; Tianhui Zhao; Chunnian Da; Jing Liu; Xiangyu Yang; Jianxiu Li; Yuxuan Liu (Chemical Engineering Journal, 2025)

Pyrite geochemistry and its implications for ore formation in reduced copper skarn systems: A case study of the Saibo deposit, Northwest China - Qing-Fei Sun; Ju-Xing Tang; Shun-Da Li; Qiu-Ming Pei; Xin-Hao Sun; Chuan Chen; Ling-Ling Gao; Xiao-Fei Du; Jin-Ling Xie (Chemical Geology, 2025)

Fabrication of Aspergillus oryzae lipase-immobilized magnetic Cu3(PO4)2∙3H2O nanoflowers for efficient synthesis of structured phospholipids - Hua-Wei Zhang; Ke Cheng; Jing-Jing Tang; Ling-Zhi Liu; Ruo-Xuan Qin; Yi-Nuo Sun; Jiang-Hua Zhang; Da-Yong Zhou (Food Bioscience, 2024)

Low lattice thermal conductivity induced by rattling-like vibration in Zintl phase Na2CaCdSb2 compound with high ZT from two-channel model - Peng Ai; Shuwei Tang; Shulin Bai; Da Wan; Wanrong Guo; Pengfei Zhang; Shizhi Dong (Chemical Engineering Journal, 2024)

Robust PD/A biofilms sustain advanced real municipal wastewater treatment: Reinforcement of interspecific communication and electron transfer - Xiaonong Zhang; Naif Abdullah Al-Dhabi; Zixuan Zhu; Xingxing Zhang; Li Zhou; Da Jin; Wangwang Tang; Duanliang Hong; Nkonogumo Paul Luchanganya; Hongbo Guo; Peng Wu; Aijie Wang (Chemical Engineering Journal, 2024)

Hydroxylated SiO2-modified {0 0 1}-TiO2 nanosheets as a surface multifunctional photocatalyst for enhanced degradation of gaseous toluene - Juntao Tang; Xinlong Wang; Yusheng Huang; Xiaopeng Du; Zhiqiao He; Da Wang; Shuang Song (Chemical Engineering Journal, 2024)

Fusion of historical survey data and remote sensing to analyze the spatiotemporal variation of altitudinal belts in the Kunlun Mountains during 2000–2020 - Jiabin Fan; Fang Zhao; Zhuangzhuang Wang; Da Wei; Yuanyuan Lian; Jiale Tang; Zhixian Zheng; Yumeng Wang (Journal of Geographical Sciences, 2024)

Vapor-phase reduction synthesis of N, S co-doped graphene/MWCNT hybrid membrane for all-solid-state supercapacitors and adsorption of organic pollutants - Erhui Zhang; Yutong Zheng; Da Xie; Yongsheng Zhou; Shengbiao Zheng; Zirong Li; Jing Tang; Jiahao Guo (Journal of Environmental Chemical Engineering, 2024)

Multi-process atmospheric particle number size distribution over the Bohai Sea: Insights from cruise and onboard unmanned aerial vehicle observations - Ziwei Liu; Hao Li; Jie Tang; Mian Wang; Haitao Zheng; Tao Luo; Xiaoquan Song; Chengfeng Liu; Guochen Wang; Xiaofei Qin; Jia Chen; Da Lu; et al. (Atmospheric Environment, 2024)

Mechanistic and synergistic aspects of ultrasonics and hydrodynamic cavitation for food processing - Jiafei Tang; Xianglu Zhu; Anet Rezek Jambrak; Da-Wen Sun; Brijesh K. Tiwari (Critical Reviews in Food Science and Nutrition, 2024)

Distributions and controlling factors of soil total nitrogen and nitrogen fractions along an altitude gradient in Qinghai-Tibet Plateau - Da Meng; Xinyu Wang; Jiayi Tang; Ning Zong; Jinjing Zhang; Nianpeng He (Journal of Soils and Sediments, 2024)

Variation in leaf N allocation and mesophyll conductance to CO2 in four tree species under low soil P stress in subtropical China - Jingchao Tang; Baodi Sun; Ruimei Cheng; Zuomin Shi; Da Luo; Shirong Liu; Mauro Centritto (Acta Physiologiae Plantarum, 2024)

Green technologies for bio-refinery in marine crustacean shell valorisation from chitin perspective - Wenrui Dong; Jiafei Tang; Janna Cropotova; Da-Wen Sun; Brijesh K. Tiwari (Trends in Food Science & Technology, 2024)

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

Genome-wide analysis of polyphenol oxidase gene family in Solanum tuberosum and functional identification of StuPPO9 in regulating tolerance to Phytophthora infestans - Ming Chi; Da Tang; Cong Xue; Jieping Huang; Bo Liu; Mengqi Cao (Physiological and Molecular Plant Pathology, 2024)

Meticulously designed red emission carbon dots as efficient and stable luminescent species for rapid latent fingerprint recognition and light emitting diodes - Jianbo Cao; Rui Chen; Linfan Wang; Haoming Xing; Houwen Hu; Xiangdong Yang; Chenjie Gu; Siyuan Tang; Da Chen (Chemical Engineering Journal, 2024)

Soil water potential measurement using fiber-optic sensing technique - Jin-Jian Xu; Chao-Sheng Tang; Qing Cheng; Farshid Vahedifard; Da-Zhan Zhang; Chang Sun; Bin Shi (Journal of Hydrology, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

The burgeoning importance of PIWI-interacting RNAs in cancer progression - Xinpei Deng; Tianle Liao; Jindong Xie; Da Kang; Yiwei He; Yuying Sun; Zhangling Wang; Yongluo Jiang; Xuan Miao; Yixuan Yan; Hailin Tang; Lewei Zhu; et al. (Science China Life Sciences, 2024)

Quantification of perfluorinated compounds in atmospheric particulate shows potential connection with environmental event - Hua Tang; Ying Wang; Shengling Si; Hongli Li; David Da Yong Chen (Journal of Environmental Sciences, 2024)

Coupling urchin-like TiO2 nanospheres with nitrogen and sulfur co-doped graphene quantum dots for visible-light-induced degradation of toluene - Juntao Tang; Jiaxin Zhu; Luzhen Liu; Lin Xia; Zhiqiao He; Da Wang; Xing Xu; Shuang Song (Chemical Engineering Journal, 2024)

Layered PrZnOX (X = P, As) compounds: Promising n-type thermoelectric materials with low lattice thermal conductivity - Xiaodong Li; Shulin Bai; Da Wan; Jingyi Zhang; Mengxiu Wu; Peng Ai; Shuwei Tang (Chemical Engineering Journal, 2024)

IFITM3 restricts porcine deltacoronavirus infection by targeting its Spike protein - Jianxiao Wu; Rongfeng Tang; Xiaorong Zhang; Mingzhe Gao; Longjun Guo; Liaoyuan Zhang; Da Shi; Xin Zhang; Hongyan Shi; Hongying Song; Li Feng; Jianfei Chen (Veterinary Microbiology, 2024)

A two-stage Fe(VI) oxidation process enhances the removal of bisphenol A for potential application - Feilong Dong; Chuyun Fu; Zhu Meng; Qiufeng Lin; Jinzhe Li; Tao Zeng; Da Wang; Juntao Tang; Shuang Song (Science of The Total Environment, 2024)

Bell pepper derived nitrogen-doped carbon dots as a pH-modulated fluorescence switching sensor with high sensitivity for visual sensing of 4-nitrophenol - Guoqiang Guo; Tingting Li; Ziyi Liu; Xinyu Luo; Ting Zhang; Siyuan Tang; Xu Wang; Da Chen (Food Chemistry, 2024)

Constructed electron-dense Mn sites in nitrogen-doped Mn3O4 for efficient catalytic ozonation of pyrazines: Degradation and odor elimination - Yinning He; Jiayi Li; Jingyu Tang; Haijun Cheng; Tao Zeng; Zhiqiao He; Da Wang; Lizhang Wang; Shuang Song; Jun Ma (Water Research, 2023)

Hydrophobic fluorine-doped carbon-wrapped TiO2 particles as efficient and stable photocatalysts for gaseous toluene degradation - Lei Lai; Juntao Tang; Jiaxin Zhu; Da Wang; Zhiqiao He; Shuang Song (Journal of Environmental Chemical Engineering, 2023)

Construction of fluorescent sensor array and three-dimensional microfluidic paper based analytical device for specific identification and visual determination of antibiotics in food - Tingting Li; Guoqiang Guo; Haoming Xing; Siyuan Tang; Houwen Hu; Linfan Wang; Xiaoqing Qian; Da Chen (Food Chemistry, 2023)

Analysis of research status and trends on marine benthic dinoflagellate toxins: A bibliometric study based on web of science database and VOSviewer - Jing-Qian Tang; Qian-Hui Shen; Yao-Yao Han; Yang Wu; Xiang-Feng He; Da-Wei Li; Yong Huang (Environmental Research, 2023)

Effect of rGO content on enhanced Photo-Fenton degradation of Venlafaxine using rGO encapsulated magnetic hexagonal FeTiO3 nanosheets - Da Wang; Stefanos Giannakis; Jingyu Tang; Kai Luo; Juntao Tang; Zhiqiao He; Shuang Song; Lizhang Wang (Chemical Engineering Journal, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

A Pore-Scale Model for Electrokinetic In situ Recovery of Copper: The Influence of Mineral Occurrence, Zeta Potential, and Electric Potential - Kunning Tang; Zhe Li; Ying Da Wang; James McClure; Hongli Su; Peyman Mostaghimi; Ryan T. Armstrong (Transport in Porous Media, 2023)
Electrokinetic in-situ recovery is an alternative to conventional mining, relying on the application of an electric potential to enhance the subsurface flow of ions. Understanding the pore-scale flow and ion transport under electric potential is essential for petrophysical properties estimation and flow behavior characterization. The governing physics of electrokinetic transport is electromigration and electroosmotic flow, which depend on the electric potential gradient, mineral occurrence, domain morphology (tortuosity and porosity, grain size and distribution, etc.), and electrolyte properties (local pH distribution and lixiviant type and concentration, etc.). Herein, mineral occurrence and its associated zeta potential are investigated for EK transport. The new Ek model which is designed to solve the EK flow in complex porous media in a highly parallelizable manner includes three coupled equations: (1) Poisson equation, (2) Nernst–Planck equation, and (3) Navier–Stokes equation. These equations were solved using the lattice Boltzmann method within X-ray computed microtomography images. The proposed model is validated against COMSOL multiphysics in a two-dimensional microchannel in terms of fluid flow behavior when the electrical double layer is both resolvable and unresolvable. A more complex chalcopyrite-silica system is then obtained by micro-CT scanning to evaluate the model performance. The effects of mineral occurrence, zeta potential, and electric potential on the three-dimensional chalcopyrite-silica system were evaluated. Although the positive zeta potential of chalcopyrite can induce a flow of ferric ion counter to the direction of electromigration, the net effect is dependent on the occurrence of chalcopyrite. However, the ion flux induced by electromigration was the dominant transport mechanism, whereas advection induced by electroosmosis made a lower contribution. Overall, a pore-scale EK model is proposed for direct simulation on pore-scale images. The proposed model can be coupled with other geochemical models for full physicochemical transport simulations. Meanwhile, electrokinetic transport shows promise as a human-controllable technique because the electromigration of ions and the applied electric potential can be easily controlled externally. Graphical abstract

In-situ constructed metallic Mo decorated MoS2 nanosheets on carbon cloth as excellent anode for efficient current generation and Cr(Ⅵ) removal - Da Liu; Chaoqun Xu; Chengyu Li; Wenkai Fang; Mei Yan; Hongwu Tang (Journal of Cleaner Production, 2023)

Enhancing energy efficiency and thermal satisfaction in office buildings: A comprehensive evaluation of space match strategy - Shiqi Ding; Chengyu Tang; Da Li; Snowil Lopes (Energy and Buildings, 2023)

The culprit for the declining performance of anaerobic reactors caused by calcification: Bioavailability deterioration - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Ecological distribution of anaerobic granular sludge towards efficient anaerobic reactor - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Hydrodynamics and sliding posture analysis of the Cambrian arthropod Ercaicunia multinodosa - Yu-Han Li; Zu-Peng Zhou; Da-You Zhai; Robert J. O'Flynn; Jun Tang; Jin-Wei Xu; Xu-Guang Zhou; Yu Liu (Palaeoworld, 2023)

Simultaneous sensing of ammonia and temperatures using a dual-mode freshness indicator based on Au/Cu nanoclusters for packaged seafood - Wenyang Zhang; Da-Wen Sun; Ji Ma; Zhiming Wang; Anjun Qin; Ben Zhong Tang (Food Chemistry, 2023)

Slope stability under the influence of irrigation and frozen stagnant water effect in Heifangtai - Guang Li; Ming-gao Tang; Ming-li Zhang; Da-lei Peng; Huan-le Zhao; Jian Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Construction of graphene quantum dots ratiometric fluorescent probe by intermolecular electron transfer effect for intelligent and real-time visual detection of ofloxacin and its L-isomer in daily drink - Changxing Wang; Feifei Qin; Siyuan Tang; Xiameng Li; Tingting Li; Guoqiang Guo; Chenjie Gu; Xu Wang; Da Chen (Food Chemistry, 2023)

In vitro digestion and fermentation combined with microbiomics and metabolomics reveal the mechanism of superfine yak bone powder regulating lipid metabolism by altering human gut microbiota - Jin Zhang; Xiaoqiong Li; Ke Zhao; Huanhuan Li; Jingnan Liu; Se Da; Dajie Ciren; Honggang Tang (Food Chemistry, 2023)

Activated cascade effect for dual-mode ratiometric and smartphone-assisted visual detection of curcumin and F− based on nitrogen-doped carbon dots - Siyuan Tang; Yiru Wang; Guoqiang Guo; Tingting Li; Haoming Xing; Houwen Hu; Xuan Leng; Chenjie Gu; Da Chen (Science of The Total Environment, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

A ratiometric fluorescent tag based on dual-emissive hydrophobic carbon dots for in-situ monitoring of seafood freshness - Wenyang Zhang; Da-Wen Sun; Ji Ma; Anjun Qin; Ben Zhong Tang (Analytica Chimica Acta, 2023)

New reduction of old glass astronomical plates of Pallas and Vesta in 1956–1994 based on Gaia DR3 catalogue - L.L. Wang; Y. Yu; Q.X. Yuldoshev; Sh.A. Ehgamberdiev; Z.J. Shang; M.T. Yang; J. Yang; S. Dong; D.M. Da; Z.H. Tang; J.H. Zhao; M.M. Muminov (Planetary and Space Science, 2023)

The involvement of an HMG-box gene in germ cell genesis in Pyropia haitanensis - Hong-Chang Ding; Long-Chen Tang; Da-Hai Gao; Xing-Hong Yan (Algal Research, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Synergy between sulfur vacancy and Schottky junction into CoB/ZnIn2S4–S photocatalysts: Oriented charge flow and regulated carriers transfer dynamics to activate reactive oxygen species generation for efficient photocatalytic disinfection - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Meng-Ke Li; Ya-Ya Yang; Ning Tang; Lu Li; Lei Zhang (Journal of Cleaner Production, 2023)

A cDNA-based reverse genetics system for feline calicivirus identifies the 3′ untranslated region as an essential element for viral replication - Jie Cheng; Aoxing Tang; Jing Chen; Da Zhang; Chunchun Meng; Chuanfeng Li; Hulai Wei; Guangqing Liu (Archives of Virology, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Synergy of surface modified nanoparticles and surfactant in wettability alteration of calcite at high salinity and temperature - Wenyue Tang; Pingkeng Wu; Chang Da; Shehab Alzobaidi; Justin Harris; Brooke Hallaman; Dongdong Hu; Keith P. Johnston (Fuel, 2023)

Stacking pattern induced high ZTs in monolayer SnSSe and bilayer SnXY (X/Y = S, Se) materials with strong anharmonic phonon scattering - Shulin Bai; Mengxiu Wu; Jingyi Zhang; Dongming Luo; Da Wan; Xiaodong Li; Shuwei Tang (Chemical Engineering Journal, 2023)

Catalytic ozonation of atrazine with stable boron-doped graphene nanoparticles derived from waste polyvinyl alcohol film: Performance and mechanism - Da Wang; Shiwen Dong; Hangkai Hu; Zhiqiao He; Feilong Dong; Juntao Tang; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2023)

Long short-term memory integrating moving average method for flood inundation depth forecasting based on observed data in urban area - Song-Yue Yang; Bing-Chen Jhong; You-Da Jhong; Tsung-Tang Tsai; Chang-Shian Chen (Natural Hazards, 2022)

Effects of the Dicranopteris linearis root system and initial moisture content on the soil disintegration characteristics of gully erosion - Ling He; Yu-song Deng; Qiu-yue Tang; Da-lan Liao; Chao Wang; Xiao-qian Duan (Journal of Mountain Science, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Actinomycin D: a novel Pseudomonas aeruginosa quorum sensing inhibitor from the endophyte Streptomyces cyaneochromogenes RC1 - Yue-Xiang Zeng; Jun-Sheng Liu; Ying-Jie Wang; Shi Tang; Da-Yong Wang; Shi-Ming Deng; Ai-Qun Jia (World Journal of Microbiology and Biotechnology, 2022)

Correction to: Protective effects of fowl‑origin cadmium‑tolerant lactobacillus against sub‑chronic cadmium‑induced toxicity in chickens - Da‑Wei Chen; Hui‑Jia Li; YinYin Liu; Li‑Na Ma; Jun‑Hua Pu; JunXian Lu; Xiu‑Jun Tang; Yu‑shi Gao (Environmental Science and Pollution Research, 2022)

Protective effects of fowl-origin cadmium-tolerant lactobacillus against sub-chronic cadmium-induced toxicity in chickens - Da-Wei Chen; Hui-Jia Li; YinYin Liu; Li-Na Ma; Jun-Hua Pu; JunXian Lu; Xiu-Jun Tang; Yu-shi Gao (Environmental Science and Pollution Research, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Mapping the spatial distribution of fossil geothermal manifestations and assessment of geothermal potential of the Tangyin rift, Southeast of Taihang Mountain in China - Joshua Mahwa; Da-jiang Li; Jian-hua Ping; Wei Leng; Jia-bo Tang; Dong-yun Shao (Journal of Mountain Science, 2022)
The spatial prediction of geothermal sites along the southeast side of Taihang Mountain in the Tangyin rift is a critical goal in the development of renewable energy resources in cities such as Hebi in Henan province, which has significant potential for geothermal energy production due to the existence of deep faults and Cenozoic volcano. The study aimed to delineate areas with high geothermal manifestations for detailed geothermal exploration and well-test drilling. To define favorable zones for geothermal potentiality, multi-source datasets were chosen to generate evidence thematic layers that demonstrate the distribution of geothermal anomalies such as geologic maps, structural maps, Land Surface Temperature maps (LST), and hydrothermal mineral alterations maps. The remote sensing and Geographical Information System (GIS) approaches were integrated to map fossil geothermal manifestations and appraise the promising geothermal zones from Landsat 8 OLI/TIRS and Advanced Spaceborne Thermal Emission and Reflection Radiometer-Digital Elevation Model (ASTER-DEM) dataset using the Analytic Hierarchy Process (AHP), which is one of the Mult-criteria Decision Making methods. Results show LST values ranging from 22.6°C to 45.4°C, with the highest values found along the faults and volcanic areas. The hydrothermal alteration minerals discriminated from band ratios of 4/2, 6/5, and 6/7 for iron oxide, ferrous minerals, and clays reveal the presence of high amount of montmorillonite and illite minerals along the faults and volcanoes which are related to hot fluid circulation from subsurface. Structural analysis shows that the major structural trend follows the NNE Tangdong and Tangxi faults, with high density on the west side of the Tangxi fault where there is good exposure of outcrop but less fault density on the east side due to sedimentation in a low land which may conceal geological structures. Lastly, all the thematic layers of geothermal factors were reclassified, ranked, and integrated by the weight overlay logic model based on the influence of geothermal suitability to map potential areas for geothermal resources whereby 5 zones were obtained ranging from very poor to very good. The promising potential sites are mostly found along the highly deep structures of the major Tangxi fault crosscutting the permeable lithology of carbonate rocks and around the Hebi volcanoes. The distribution of hot springs and geothermal wells of the Hebi field were correlated and verified against the potential geothermal anomalies map. The overall integrated method proposes an advanced technique for designing the Tangyin rift’s exploration plan and development actions for geothermal resources utilization, which can be used for exploration of any unveiling geothermal potential sites.

Main lymphocyte subpopulations in cerebrospinal fluid and peripheral blood in HIV-1 subtypes C and B - Sergio M. de Almeida; Miriam Perlingeiro Beltrame; Bin Tang; Indianara Rotta; Yara Schluga; Julie Lilian P. Justus; Maria Tadeu da Rocha; Ian Abramson; Florin Vaida; Rachel Schrier; Ronald J. Ellis (Journal of NeuroVirology, 2022)

Electrokinetic stabilization of marine clayey soil using magnesium chloride solution: A green soil stabilizer - Yongqiang Tang; Ningwei Wang; Feng Xu; Da Teng; Xiaoming Cui (Marine Georesources & Geotechnology, 2022)

Generation and Role of Calpain-Cleaved 17-kDa Tau Fragment in Acute Ischemic Stroke - Ying-Da Chen; Po-Yuan Huang; Chien-Sung Chiang; Yi-Shuian Huang; Sung-Chun Tang (Molecular Neurobiology, 2021)

3,5,4′-Trimethoxy-trans-stilbene loaded microemulsion for cutaneous melanoma therapy by transdermal drug delivery - Jun-Yong Wu; Jia-Xin Cai; Yong-Jiang Li; Xiong-Bin Hu; Xin-Yi Liu; Jie-Min Wang; Tian-Tian Tang; Da-Xiong Xiang (Drug Delivery and Translational Research, 2021)

Critical tension crack depth in rockslides that conform to the three-section mechanism - Guoqing Chen; Peng Tang; Runqiu Huang; Dong Wang; Zhiheng Lin; Da Huang (Landslides, 2021)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Elastic properties of transversely isotropic rocks containing aligned cracks and application to anisotropy measurement - Song Xu; Yuan-Da Su; Xiao-Ming Tang (Applied Geophysics, 2020)

Effects of Organic Copper on Growth Performance and Oxidative Stress in Mice - Mingyu Zhi; Ping Tang; Ying Liu; Da He; Suxia Zheng (Biological Trace Element Research, 2020)

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

Ore genesis and tectonic setting of the Laojiagou porphyry molybdenum deposit, Inner Mongolia, China: evidence from geology, fluid inclusions, H–O isotopes, zircon U–Pb geochronology, and geochemistry - Wen-Hao Tang; Jian Li; Ke-Yong Wang; Shun-Da Li; Wen-Yan Cai; Han-Lun Liu; Yi-Cun Wang (Arabian Journal of Geosciences, 2019)

IGF-1R/β-catenin signaling axis is involved in type 2 diabetic osteoporosis - Zhi-da Zhang; Hui Ren; Wei-xi Wang; Geng-yang Shen; Jin-jing Huang; Mei-qi Zhan; Jing-jing Tang; Xiang Yu; Yu-zhuo Zhang; De Liang; Zhi-dong Yang; Xiao-bing Jiang (Journal of Zhejiang University-SCIENCE B, 2019)

Application of four-component dipole shear reflection imaging to interpret the geological structure around a deviated well - Sheng-Qing Lee; Ming Chen; Xi-Hao Gu; Yuan-Da Su; Xiao-Ming Tang (Applied Geophysics, 2019)

Utilization of Industrial Waste in Cement in a Marine Environment with a Tropical Climate - Thi Chu; Jinhai Zheng; Da Chen; Thi Nguyen; Elsafi Elbashiry; Van Tang (Journal of Marine Science and Engineering, 2019)
This novel study on cement paste material was conducted with the aim of keeping up with the rapid development of urban construction and contributing to the continuous improvement of building materials to overcome environmental issues. In this study, several kinds of industrial waste were used to enhance the properties of cement paste for application in a marine environment with a tropical climate, such as in Vietnam. This study focuses on evaluating the properties of cement paste containing cement replacement combining 0–30% fly ash, 0–10% silica fume, and plasticizer accounting for 0.3% and 0.4% of the binder by mass. Water demand, chloride ion and sulfate ion permeability, and microstructural properties of the cement paste were determined by thermogravimetric analysis (TGA), X-ray diffraction (XRD), and scanning electron microscope (SEM) and they were investigated after 28 and 56 days. The test results show that an optimum mixture could be obtained with the use of 20% fly ash, 10% silica fume (replacing Portland cement), and 0.4% plasticizer. The application of such materials to sea dikes affected by a tropical climate (characterized by heat, humidity, salty seawater, many big storms, large waves, and strong tides) was investigated for four years on the Vietnamese coast. The test results indicate that fly ash and silica fume can improve the corrosion and abrasion resistance of concrete in coastal areas with a tropical climate, such as in Vietnam.

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

Investigation of the anisotropy of black shale in dynamic tensile strength - Xiaoshan Shi; Da’an Liu; Wei Yao; Yirui Shi; Tiewu Tang; Bonan Wang; Weige Han (Arabian Journal of Geosciences, 2018)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Biodegradation of sulfamethazine by an isolated thermophile–Geobacillus sp. S-07 - Lan-jia Pan; Xiao-da Tang; Chun-xing Li; Guang-wei Yu; Yin Wang (World Journal of Microbiology and Biotechnology, 2017)

Amygdalin inhibits HSC-T6 cell proliferation and fibrosis through the regulation of TGF-β/CTGF - Huanhuan Luo; Liang Li; Jianbang Tang; Fengxue Zhang; Fang Zhao; Da Sun; Fengling Zheng; Xinhua Wang (Molecular & Cellular Toxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Complete mitochondrial genome sequence of Tridentiger bifasciatus and Tridentiger barbatus (Perciformes, Gobiidae): a mitogenomic perspective on the phylogenetic relationships of Gobiidae - Xiaoxiao Jin; Rixin Wang; Tao Wei; Da Tang; Tianjun Xu (Molecular Biology Reports, 2015)

Long-term morphological response to dredging including cut-across-shoal in a tidal channel-shoal system - Yu-Hai Wang; Chong-Hao Wang; Li-Qun Tang; Da-Bin Liu; Chuan-Sheng Guo; Chun-Jing Liu; Hui-Ming Zhao (Ocean Dynamics, 2014)

The “valley economy” model of regional development: A case study of mountain areas in Beijing, northern China - Chun-la Liu; Ming-xing Chen; Zhi-peng Tang; Wei-dong Liu; Da-dao Lu; Yi-feng Zhang (Journal of Mountain Science, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

A gain-of-function mutation in IAA8 alters Arabidopsis floral organ development by change of jasmonic acid level - Jing Wang; Da-Wei Yan; Ting-Ting Yuan; Xiang Gao; Ying-Tang Lu (Plant Molecular Biology, 2013)

Characterization, genomic organization, and expression profiles of MyD88, a key adaptor molecule in the TLR signaling pathways in miiuy croaker (Miichthys miiuy) - Da Tang; Yunhang Gao; Rixin Wang; Yuena Sun; Tianjun Xu (Fish Physiology and Biochemistry, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Pseudonocardia yuanmoensis sp. nov., a novel actinobacterium isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Da-Qiao Wei; En-Min Zhou; Xia Tang; Juan Cheng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Genetic diversity of four new species related to southwestern Sichuan buckwheats as revealed by karyotype, ISSR and allozyme characterization - Mei-Liang Zhou; Da-Quan Bai; Yu Tang; Xue-Mei Zhu; Ji-Rong Shao (Plant Systematics and Evolution, 2012)

Gastrodin protects against cardiac hypertrophy and fibrosis - Chunming Shu; Changgui Chen; Da-Ping Zhang; Haipeng Guo; Heng Zhou; Jing Zong; Zhouyan Bian; Xuan Dong; Jia Dai; Yan Zhang; Qizhu Tang (Molecular and Cellular Biochemistry, 2012)

Immunolocalization of chloride transporters to gill epithelia of euryhaline teleosts with opposite salinity-induced Na+/K+-ATPase responses - Cheng-Hao Tang; Lie-Yueh Hwang; I-Da Shen; Yu-Hui Chiu; Tsung-Han Lee (Fish Physiology and Biochemistry, 2011)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

Polyethylenimine-cyclodextrin-tegafur conjugate shows anti-cancer activity and a potential for gene delivery - Qi-da Hu; Hui Fan; Wei-jian Lou; Qing-qing Wang; Gu-ping Tang (Journal of Zhejiang University-SCIENCE B, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Retrieval of chlorophyll a concentration from a fluorescence enveloped area using hyperspectral data - Fen-Fen Liu; Chu-Qun Chen; Shi-Lin Tang; Da-Zhao Liu (International Journal of Remote Sensing, 2011)

An equivalent-tool theory for acoustic logging and applications - Yuan-Da Su; Xiao-Ming Tang; Chuang Hei; Chun-Xi Zhuang (Applied Geophysics, 2011)

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Stereological and allometric studies on neurons and axo-dendritic synapses in the superior cervical ganglia of rats, capybaras and horses - Andrzej Loesch; Terry M. Mayhew; Helen Tang; Fernando V. Lobo Ladd; Aliny A. B. Lobo Ladd; Mariana Pereira de Melo; Andrea Almeida P. da Silva; Antonio Augusto Coppi (Cell and Tissue Research, 2010)

Trigonostemon tuberculatus (Euphorbiaceae), a peculiar new species from Yunnan Province, China - Du Fan; He Ju; Yang Shao-Yong; Cheng Xia; Zhang Da-Cai; Tang Ye-Na (Kew Bulletin, 2010)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Evaluation models of insurers’ risk management based on large system theory - Xiaobei Liang; Demian Chen; Da Ruan; Bingyong Tang (Stochastic Environmental Research and Risk Assessment, 2009)

Monosialoanglioside (GM1) prevents lead-induced neurotoxicity on long-term potentiation, SOD activity, MDA levels, and intracellular calcium levels of hippocampus in rats - Jia-Qi She; Ming Wang; Da-Miao Zhu; Mingliang Tang; Ju-Tao Chen; Lang Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Targeted migration and differentiation of engrafted neural precursor cells in amyloid β-treated hippocampus in rats - Jun Tang; Hai-Wei Xu; Xiao-Tang Fan; Zhi-Fang Li; Da-Bing Li; Li Yang; Guang-Ji Zhou (Neuroscience Bulletin, 2007)

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface - Da Li; Qing-qing Wang; Gu-ping Tang; Hong-liang Huang; Fen-ping Shen; Jing-zhong Li; Hai Yu (Journal of Zhejiang University-SCIENCE B, 2006)

Flexible design of a rock slope abutment at the Wuqiangxi Hydroelectric Power Station - Yanjun Shang; Hyeong-Dong Park; Zhifa Yang; Da’an Liu; Chunhua Tang (Bulletin of Engineering Geology and the Environment, 2006)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)